Global research trend of Herpes simplex keratitis: a bibliometric analysis and visualization from 1941 to 2024 - Song, Ke; Li, Shujiao; Liu, Jian; Kang, Zefeng (Frontiers in Medicine, 2025)
ObjectiveHerpes simplex keratitis (HSK), caused by the herpes simplex virus (HSV), is a leading cause of infectious blindness worldwide. This study aims to explore the research trends, key contributors, and emerging areas of focus in HSK research through bibliometric analysis.MethodsPublications related to HSK from 1941 to 2024 were retrieved from the Web of Science Core Collection (WoSCC). Bibliometric and visual analyses were conducted using VOSviewer, CiteSpace, and R 4.3.3.ResultsA total of 1,076 publications on HSK were identified. The top three contributing countries were the United States (267 papers), China (99), and Japan (64). Harvard University was the leading institution with 75 publications, while the American Journal of Ophthalmology emerged as the most influential journal, boasting an h-index of 29. Kaufman, HE, was the most cited author, with 1,988 citations. The top three keywords were “infection” (82), “stromal keratitis” (73), and “penetrating keratoplasty” (62). Burst keyword analysis indicated a growing interest in terms such as “outcome” and “ultraviolet A” since 2018.ConclusionThis bibliometric analysis underscores two primary research areas in HSK: the clinical management of stromal keratitis and infection, as well as the mechanisms of HSK recurrence, which include strategies for preventing reactivation and managing immune rejection. Future research is anticipated to focus on innovative treatments, particularly ultraviolet A therapy.